Non-Puerperal Uterin Inversion Caused by Myoma of the Uterus - Sunullah Soysal; Gökçe Anık İlhan; Mehmet Vural; Begüm Yıldızhan; Tanju Pekin (Medical Network, 2016)
Non puerperal uterine inversion is a rare event and mostly caused by uterine myomas. Herein a case of uterine inversion caused by myoma protruding through vagina is presented. Uterine inversion should be considered in patients with uterine mass protruding to vagina.